2009
DOI: 10.1073/pnas.0903078106
|View full text |Cite
|
Sign up to set email alerts
|

Study of free oligosaccharides derived from the bacterial N -glycosylation pathway

Abstract: The food-borne pathogen Campylobacter jejuni is one of the leading causes of bacterial gastroenteritis worldwide and the most frequent antecedent in neuropathies such as the Guillain-Barré and Miller Fisher syndromes. C. jejuni was demonstrated to possess an N-linked protein glycosylation pathway that adds a conserved heptasaccharide to >40 periplasmic and membrane proteins. Recently, we showed that C. jejuni also produces free heptasaccharides derived from the N-glycan pathway reminiscent of the free oligosac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 53 publications
1
64
1
Order By: Relevance
“…Among OST subunits, we identified the catalytic Stt3 subunit as the enzyme responsible for the generation of fOSs. It has been shown that in the food-borne bacterial pathogen Campylobacter jejuni, the Stt3 ortholog, PglB, is responsible for the generation of fOSs (37). Periplasmic fOSs are thought to be important for the modulation of osmolarity, whereas the functional importance of fOSs in the ER remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Among OST subunits, we identified the catalytic Stt3 subunit as the enzyme responsible for the generation of fOSs. It has been shown that in the food-borne bacterial pathogen Campylobacter jejuni, the Stt3 ortholog, PglB, is responsible for the generation of fOSs (37). Periplasmic fOSs are thought to be important for the modulation of osmolarity, whereas the functional importance of fOSs in the ER remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As inhabitants of the avian and human intestinal tracts, C. jejuni strains are in competition for iron, not only with other intestinal microbes but also with the host. To survive within this competitive environment, C. jejuni has evolved mechanisms for acquiring iron from other bacterial species as well as from human and avian hosts (452). In contrast, as the lone known bacterial resident of the gastric mucosa, H. pylori competes for iron solely with the human host.…”
Section: Discussionmentioning
confidence: 99%
“…By using semiquantitative mass spectrometry, Nothaft et al discovered that approximately 90% of the glycan was found in a free oligosaccharide (fOS) form in the periplasm, and only 10% of the glycan was found to be N-linked to protein (452). Like that of the Nlinked glycan, production of the fOS is dependent on many Pgl enzymes, including PglB, which suggests that PglB may promote fOS release from the lipid carrier in the absence of a protein acceptor (Fig.…”
Section: N-linked Protein Glycosylation System Of C Jejunimentioning
confidence: 99%
See 1 more Smart Citation
“…This is thought to be a mechanism of coping with salt stress and an evolutionary measure to ensure maintenance of N-linked protein glycosylation. 73 Of the proteins an acetamidino substitution, legionaminic acid, and bacillosamine, the latter two of which are involved in C. jejuni protein glycosylation but have never before been seen in H. pylori glycoproteins.…”
Section: Protein Glycosylationmentioning
confidence: 99%